Incidence of pediatric multiple sclerosis in Iran from 2000 to 2019 - Nasehi, Mohammad Mahdi; Nikkhah, Ali; Moosazadeh, Mahmood; Saket, Sasan; Alizadeh-Navaei, Reza (Iranian Journal of Child Neurology, 2022)
Objectives Due to a lack of data on pediatric multiple sclerosis (MS) epidemiology in Iran, this study aimed to determine the incidence rate of pediatric MS in Iran. Materials & Methods All the data of the patients with MS registered in the Ministry of Health and Medical Education of Iran for 20 years were collected in this study; therefor; those born in 1982 and diagnosed with the disease and treated since 2000 were included in this study. The collected variables were patients’ age at the time of diagnosis, gender, year of diagnosis, urban or rural residency, and province of residence. Additionally, agespecific incidence rates per 100,000 of the population were calculated. Results This study was performed on 4544 cases of pediatric MS within 2000- 2019, of which 997 patients (21.9%) were male. The mean age of the patients with MS at the time of diagnosis was 14.3±4.6 years, and 4414 children (97.1%) lived in urban areas. The incidence rate of pediatric MS in Iran during 20 years increased from 0.26 per 100,000 of the population in 2000 to 1.53 in 2019. Conclusion The incidence of pediatric MS in Iran is high, and the development of diagnostic practices in the past decade in Iran has contributed to the detection of this high incidence.